ANALYSIS OF THE LOST OF READING CULTURE IN SMP N.1 ATAP TAMPAHAN LIBRARY - Bonari Tambunan; Rotua Hutasoit; Friscelly Siahaan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2022)
This study has two main objectives proposed by the researcher, namely, (1) to analyze the causes of the disappearance of reading culture in the library of Smp N.1 Atap Tampahan (2) to analyze the main factors the lost reading culture to reappear. Regarding the data collection method, the researcher used interviews with the librarian and one of the students who happened to visit the library. The researcher used a descriptive qualitative approach. The researcher used observation, questionnaires, interviews, and documentary to collect the data.The results showed that in attracting students' interest in reading at school, it turned out that library improvements were needed starting from the available books, neat and clean rooms and friendly librarian.